Psychological resilience in sport performers: a review of stressors and protective factors - Sarkar, M.; Fletcher, D. (Journal of Sports Sciences, 2014)
Psychological resilience is important in sport because athletes must utilise and optimise a range of mental qualities to withstand the pressures that they experience. In this article, we discuss psychological resilience in sport performers via a review of the stressors athletes encounter and the protective factors that help them withstand these demands. It is hoped that synthesising what is known in these areas will help researchers gain a deeper profundity of resilience in sport, and also provide a rigorous and robust foundation for the development of a sport-specific measure of resilience. With these points in mind, we divided the narrative into two main sections. In the first section, we review the different types of stressors encountered by sport performers under three main categories: competitive, organisational and personal. Based on our recent research examining psychological resilience in Olympics champions, in the second section we discuss the five main families of psychological factors (viz. positive personality, motivation, confidence, focus, perceived social support) that protect the best athletes from the potential negative effect of stressors. It is anticipated that this review will help sport psychology researchers examine the interplay between stressors and protective factors, which will, in turn, focus the analytical lens on the processes underlying psychological resilience in athletes.